Nitric oxide inhibitory activity and antioxidant evaluations of 2-benzoyl-6-benzylidenecyclohexanone analogs, a novel series of curcuminoid and diarylpentanoid derivatives - Leong, Sze Wei; Mohd Faudzi, Siti Munirah Mohd Faudzi; Abas, Faridah; Mohd Aluwi, Mohd Fadhlizil Fasihi; Rullah, Kamal; Lam, Kok Wai; Abdul Bahari, Mohd Nazri; Ahmad, Syahida; Tham, Chau Ling; Shaari, Khozirah; Lajis, Nordin H. (Elsevier, 2015)
A series of twenty-four 2-benzoyl-6-benzylidenecyclohexanone analogs were synthesized and evaluated for their nitric oxide inhibition and antioxidant activity. Six compounds (3, 8, 10, 17, 18 and 19) were found to exhibit significant NO inhibitory activity in LPS/IFN-induced RAW 264.7 macrophages, of which compound 10 demonstrated the highest activity with the IC50 value of 4.2 ± 0.2 lM. Furthermore, two compounds (10 and 17) displayed antioxidant activity upon both the DPPH scavenging and FRAP analyses. However, none of the 2-benzoyl-6-benzylidenecyclohexanone analogs significantly scavenged NO radical. Structure-activity comparison suggested that 3,4-dihydroxylphenyl ring is crucial for bioactivities of the 2-benzoyl-6-benzylidenecyclohexanone analogs. The results from this study and the reports from previous studies indicated that compound 10 could be a candidate for further investigation on its potential as a new anti-inflammatory agent